The influence of contemporary and emerging factors on blood lead concentrations among young males in conflict with the law: a case study from a middle-income country - Mbonane, Thokozani P.; Swart, Andre; Mathee, Angela; Naicker, Nisha (Frontiers in Epidemiology, 2025)
IntroductionScientific evidence shows that contemporary and emerging factors contribute to high blood lead concentrations in different populations. The study aimed to determine blood lead concentrations and risk factors associated with high blood lead concentrations among young males in conflict with the law.MethodsA cross-sectional analytical study was conducted among 192 conveniently selected participants from two youth secure (correctional) facilities in Gauteng Province, South Africa.ResultsThe study's overall blood lead concentration median was 3.30 μg/dl, ranging from 0.85 to 48.11 μg/dl. Young males born outside of South Africa (median = 8.78 μg/dl) and in villages (median = 4.95 μg/dl), working before coming to the facility (median = 5.23 μg/dl) and involvement in illegal mining (median = 9.00 μg/dl) had high blood lead concentrations in this study. Contemporary and emerging risk factors such as being born outside the country (AOR: 3.10, 95%CI: 1.01–1.88), involvement in illegal mining activities (AOR: 1.36, 95%CI: 1.14–1.91) and staying in a house with peeling paint on the outside (AOR: 2.26, 95%CI: 1.12–4.30) were found to influence blood lead concentration.DiscussionThe study findings show that contemporary (co-existing) and emerging factors influence blood lead concentrations. Therefore, there is a need to investigate these factors further in communities that may be affected. Lastly, there is a need for a holistic approach involving multiple sectors to introduce human lead concentration screening and preventive programmes.